Rewired phenolic metabolism and improved saccharification efficiency of a Zea mays cinnamyl alcohol dehydrogenase 2 (zmcad2) mutant. (9th January 2021) - Liu, Xinyu; Van Acker, Rebecca; Voorend, Wannes; Pallidis, Andreas; Goeminne, Geert; Pollier, Jacob; Morreel, Kris; Kim, Hoon; Muylle, Hilde; Bosio, Mickael; Ralph, John; Vanholme, Ruben; et al.
Summary: Lignocellulosic biomass is an abundant byproduct from cereal crops that can potentially be valorized as a feedstock to produce biomaterials. Zea mays CINNAMYL ALCOHOL DEHYDROGENASE 2 ( ZmCAD2 ) is involved in lignification, and is a promising target to improve the cellulose‐to‐glucose conversion of maize stover. Here, we analyzed a field‐grown zmcad2 Mutator transposon insertional mutant. Z mcad2 mutant plants had an 18% lower Klason lignin content, whereas their cellulose content was similar to that of control lines. The lignin in zmcad2 mutants contained increased levels of hydroxycinnamaldehydes, i.e. the substrates of ZmCAD2, ferulic acid and tricin. Ferulates decorating hemicelluloses were not altered. Phenolic profiling further revealed that hydroxycinnamaldehydes are partly converted into (dihydro)ferulic acid and sinapic acid and their derivatives in zmcad2 mutants. Syringyl lactic acid hexoside, a metabolic sink in CAD‐deficient dicot trees, appeared not to be a sink in zmcad2 maize. The enzymatic cellulose‐to‐glucose conversion efficiency was determined after 10 different thermochemical pre‐treatments. Zmcad2 yielded significantly higher conversions compared with controls for almost every pre‐treatment. However, the relative increase in glucose yields after alkaline pre‐treatment was not higher than the relative increase when no pre‐treatment was applied, suggesting that the positive effect of the incorporation of hydroxycinnamaldehydes was leveled off by the negative effect of reduced p ‐coumarate levels in the cell wall. Taken together, our results reveal how phenolic metabolism is affected in CAD‐ deficient maize, and further support mutating CAD genes in cereal crops as a promising strategy to improve lignocellulosic biomass for sugar‐platform biorefineries. Significance Statement: Maize stover is a byproduct of grain production that is currently underutilized as a feedstock in the industry because of its difficulty to be processed into fermentable sugars. Field‐grown Zmcad2 maize mutants deposit less lignin and accumulate a wide range of soluble feruloyl and sinapoyl hexose conjugates. The shifts in lignin composition and the reduced lignin content of Zmcad2 resulted in a higher saccharification efficiency after eight out of the 10 biomass pre‐treatments tested.